PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL PEMODERASI - Lestari, Hesty Mey; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out whether the profitability moderates the corporate social responsibility(CSR) to the firm value on banking companies which are listed in Indonesia Stock Exchange. This research is aquantitative research. The population is all banking companies which area listed in Indonesia Stock Exchange in2011-2014 periods. The sample collection technique has been done by using purposive sampling and 27 bankingcompanies have been selected as samples. The data analysis technique has been done by using multipleregressions analysis and the hypothesis test is carried out by using SPSS 20 version. Based on the result ofmodel feasibility test, it shows that the regressions models which have been generated is feasible and it can beused for further analysis.The measurement of corporate social responsibility variable has been carried out byusing Corportae Social Responsibility Indeks (CSRI), the measurement of profitability has been done by usingreturn on equity (ROE) and firm value has been done by using Tobinâs Q. Based on the result of hypothesis test,it can be concluded that CSR (Corportae Social Responsibility) has positive influence to the firm value.Profitability as the moderating variable can influence the correlation of corporate social responsibility and firmvalue.Keywords: CSR, profitability, firm value